Analysis of Learning Motivation and Self-Confidence in Mathematics Learning Among Elementary School Students in Bogor Regency - Fathunnisa, Mega; Wahyudin, Wahyudin (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
Learning motivation and self-confidence are crucial qualities that students must possess as they serve as capital for effective learning, particularly in Mathematics. This research aims to analyze the learning motivation and self-confidence of Elementary School students in Mathematics. The research population includes 54 individuals, comprising fourth and sixth-grade students of SDN Tegal 02, Kemang District, Bogor Regency. This research employed a descriptive quantitative approach and used a questionnaire as the research instrument. Descriptive quantitative analysis was conducted for data analysis. The results indicate that the learning motivation and self-confidence of SDN Tegal 02 students in mathematics fall within the moderate criteria, with 50% for learning motivation and 87% for self-confidence. In terms of learning motivation, the only moderate indicator is a conducive learning environment, with a percentage of 62.96%. Regarding self-confidence, five out of six indicators are in the moderate criteria, particularly in independence, with a percentage of 81.5%. These indicators highlight the significance of the teacher's role in creating a conducive learning environment and using appropriate models to enhance students' learning motivation and self-confidence in mathematics education. In SDN Tegal 02, Bogor Regency, female students tend to have higher motivation and confidence than male students. However, both male and female students with high motivation levels also exhibit high self-confidence, as do those with moderate and low motivation levels.